Interaction of light with hematite hierarchical structures: Experiments and simulations - Distaso, Monica; Zhuromskyy, Oleksandr; Seemann, Benjamin; Pflug, Lukas; Mackovic, Mirza; Encina, Ezequiel Roberto; Klupp Taylor, Robin; Müller, Rolf; Leugering, Günter; Spiecker, Erdmann; Peschel, Ulf; Peukert, Wolfgang (Journal of Quantitative Spectroscopy & Radiative Transfer, 2017)
Mesocrystalline particles have been recognized as a class of multifunctional materials with potential applications in different fields. However, the internal organization of nanocomposite mesocrystals and its influence on the final properties have not yet been investigated. In this paper, a novel strategy based on electrodynamic simulations is developed to shed light on how the internal structure of mesocrystals influences their optical properties. In a first instance, a unified design protocol is reported for the fabrication of hematite/PVP particles with different morphologies such as pseudo-cubes, rods-like and apple-like structures and controlled particle size distributions. The optical properties of hematite/PVP mesocrystals are effectively simulated by taking their aggregate and nanocomposite structure into consideration. The superposition T-Matrix approach accounts for the aggregate nature of mesocrystalline particles and validate the effective medium approximation used in the framework of the Mie theory and electromagnetic simulation such as Finite Element Method. The approach described in our paper provides the framework to understand and predict the optical properties of mesocrystals and more general, of hierarchical nanostructured particles.
Keywords: Effective medium approximation; FEM; Maxwell-Garnett theory; Mesocrystals; Scattering; T-Matrix

Solar spectral conversion for improving the photosynthetic activity in algae reactors - Wondraczek, Lothar; Batentschuk, Miroslaw; Schmidt, Markus A.; Borchardt, Rudolf; Scheiner, Simon; Seemann, Benjamin; Schweizer, Peter; Brabec, Christoph (Nature Communications, 2013)
Sustainable biomass production is expected to be one of the major supporting pillars for future energy supply, as well as for renewable material provision. Algal beds represent an exciting resource for biomass/biofuel, fine chemicals and CO storage. Similar to other solar energy harvesting techniques, the efficiency of algal photosynthesis depends on the spectral overlap between solar irradiation and chloroplast absorption. Here we demonstrate that spectral conversion can be employed to significantly improve biomass growth and oxygen production rate in closed-cycle algae reactors. For this purpose, we adapt a photoluminescent phosphor of the type Ca SrEuS, which enables efficient conversion of the green part of the incoming spectrum into red light to better match the Q peak of chlorophyll b. Integration of a Ca SrEuS backlight converter into a flat panel algae reactor filled with Haematococcus pluvialis as a model species results in significantly increased photosynthetic activity and algae reproduction rate. © 2013 Macmillan Publishers Limited. All rights reserved.